The impact of international trade relations on French borrowings into English in the sparkling wine industry: A corpus-driven study conducted by a terminologist - Piotr Nagórka (LingBaW)
This article serves several purposes. First, it aims to consolidate the view that knowledge models make effective diagnostic tools that terminologists can use in their attempt to find answers to research questions about communication in professional fields. Secondly, the article serves to demonstrate the results of preliminary research into professional communication in the sparkling wine industry, with the working English-language model showing the presence of borrowings from French, the industry’s leading language. Notably, the percentage of French borrowings in the sparkling wine industry, an integral part of the domain of special wines, has been found to be greater than the percentage of loanwords from Portuguese and Spanish, leading languages in the fortified wine industries representing the same industrial domain (OIV 2022: I.1.4-1). This finding bears out the view that communication in a professional field may be typified by more than one leading (national) language. Moreover, outcomes of the study of encyclopaedic knowledge on sparkling wines, when combined with the results of the study into communication in the fortified wines sector (Nagórka 2021, Nagórka 2023: 94–105), indicate that the history of commercial ties between pertinent language communities (English-speaking community with French-, Portuguese- and Spanish-speaking communities) may be reflected in the scale of borrowing into English for professional purposes. The rise in borrowing from leading languages seems inversely proportional to the intensity of (amicable) trade relations between the communities concerned, a hypothesis that may contribute to explaining the observed differences in borrowability.